Process and Criteria for Recruitment of Partai Keadilan Sejahtera Legislative Member Candidates for Lampung Province in the 2024 Election - Silvi, Sevtia Amalia; Darmastuti, Ari; Cahyadi, Robi (CV. Rayyan Dwi Bharata, 2024)
PKS Lampung Province is one of the political parties participating in the 2024 elections, but as a PKS cadre party it actually provides the same candidacy opportunities for old cadres and new cadres who register themselves when they want to nominate as legislative members of PKS without going through the selection stage or in-depth introduction to the vision and mission of PKS. The focus of this research is to examine the process and criteria for recruiting legislative candidates as determined by DPW PKS Lampung in facing the 2024 elections. This research uses the recruitment process theory according to Michael Rush and Philip Althoff, namely the open recruitment process and closed recruitment process and recruitment criteria based on rational theory. choices according to Barbara Gaddes are partisanship, meritocratic, survival, and compartmentalization. The research method used is descriptive qualitative. The data used is primary data obtained through interviews with research informants and observations with DPW PKS Lampung regarding the recruitment process and criteria, as well as secondary data obtained through documentation such as the list of PKS legislative candidates, the General Election Law, General Election Commission Regulations, and etc. The results of the research show that the Lampung PKS DPW uses a closed recruitment process, namely that the legislative member candidates nominated by PKS are all internal PKS members, because PKS does not nominate candidates independently. The recruitment criteria set are partisanship criteria because all candidates do not go through the selection stage, the priority is only on how much vote support they are able to collect, as well as survival criteria for candidates who are recommended directly by PKS as legislative candidates through providing financial assistance in fulfilling all nomination processes.